2020
DOI: 10.1016/s2214-109x(20)30229-1
|View full text |Cite
|
Sign up to set email alerts
|

Early estimates of the indirect effects of the COVID-19 pandemic on maternal and child mortality in low-income and middle-income countries: a modelling study

Abstract: Background While the COVID-19 pandemic will increase mortality due to the virus, it is also likely to increase mortality indirectly. In this study, we estimate the additional maternal and under-5 child deaths resulting from the potential disruption of health systems and decreased access to food.Methods We modelled three scenarios in which the coverage of essential maternal and child health interventions is reduced by 9•8-51•9% and the prevalence of wasting is increased by 10-50%. Although our scenarios are hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
1,188
5
65

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,201 publications
(1,276 citation statements)
references
References 16 publications
18
1,188
5
65
Order By: Relevance
“…Post‐epidemic data analysis revealed that deaths due to non‐Ebola conditions exceeded those due to Ebola virus infection because the national healthcare systems failed to provide essential care to non‐Ebola patients 8 . Similarly, the indirect effects of COVID‐19 pandemic on child mortality are expected to be devastating due to widespread disruption to health systems in the low‐resource countries 1 . Early estimates represent a 9.8%‐44.7% increase in child deaths per month due to reduced care‐seeking for common childhood killer diseases in countries with poor healthcare systems 1 .…”
Section: Figurementioning
confidence: 99%
“…Post‐epidemic data analysis revealed that deaths due to non‐Ebola conditions exceeded those due to Ebola virus infection because the national healthcare systems failed to provide essential care to non‐Ebola patients 8 . Similarly, the indirect effects of COVID‐19 pandemic on child mortality are expected to be devastating due to widespread disruption to health systems in the low‐resource countries 1 . Early estimates represent a 9.8%‐44.7% increase in child deaths per month due to reduced care‐seeking for common childhood killer diseases in countries with poor healthcare systems 1 .…”
Section: Figurementioning
confidence: 99%
“…Globally, the COVID‐19 pandemic has already led to major increases in unemployment (International Labour Organization, 2020a) and is expected to lead to unprecedentedincreases in poverty (International Labour Organization, 2020b; International Monetary Fund, 2020), as well as poor physical and mental health. COVID‐19 is projected to hit particularly hard the food, nutrition, and health security of vulnerable groups including young children, pregnant and lactating women further exacerbating social and health inequities (Roberton et al, 2020; UNICEF, WHO, WFP, &FAO, 2020). One mechanism by which this is likely to happen is through a major decline in food security which exists when ‘all people, at all times, have physical, social, and economic access to sufficient, safe, and nutritious food which meets their dietary needs and food preferences for an active and healthy life’ (FAO, 2006).…”
mentioning
confidence: 99%
“…A major concern is the increasing evidence of the high risk of major disruptions in maternal, newborn, and child health services (MNCH), particularly in low‐ and middle‐ income countries during COVID‐19 times (Roberton et al, 2020). This may be due in part due to fears related to seeking health care, but may also be due to limited transportation availability during lockdowns as well as limited health service provision as health facilities turn their attention to the pandemic.…”
mentioning
confidence: 99%
“…It is therefore imperative that other methods of estimating the burden of COVID‐19 in LMICs may have to be utilised including syndromic surveillance as well as modelling data. However, modelling in COVID‐19 has led to different predictions depending on assumptions made 3 . It is therefore difficult to tell which path the pandemic will follow in reality.…”
mentioning
confidence: 99%